The Monetary Policy Regime and Banking Spreads in Barbados - Valderrama, Laura (IMF Working Papers; Working Paper, 2006)
The paper analyzes the determinants of banking spreads in Barbados, with a view to identifying the role of the monetary policy regime in explaining high spreads. The paper finds that interest rate spreads for Barbados are higher than would be suggested by its macroeconomic performance. Banking concentration and bank-specific variables, including bank size and provisions for nonperforming loans, do not have an important role in explaining variations in bank spreads. Rather, it appears that monetary policy variables, such as reserve requirements and capital controls, are the most important determinants of spreads.